Effectiveness and Efficiency of using BIO-Smart Planters for Eggplant Farmers (Solanum melongena L.) - Juita Rahmadani Manik; Nana Trisna Mei Kabeakan; Adinda Nirwana Lubis (JASc (Journal of Agribusiness Sciences), 2020)
One of the causes of the decline in production of eggplant plants is pests, namely aphids (Aphis gossypii), trips (Thrips sp), whitefly (Bemisia tabaci), and mites (Tetranychus sp). These pests attack eggplant plants both in the vegetative and generative phases, which attack the shoots of the leaves and stems of eggplant plants so that there is a deviation in the growth of eggplant plants, namely experiencing frizzy or wrinkled leaves. The high consumer demand for eggplant fruit which increases every year makes farmers have to be able to meet the market demand. Indonesia tends to be still low in the production of eggplant plants to be able to meet the world's needs, namely by 1% Vegetable pesticides are pesticides whose basic ingredients come from natural ingredients such as plants or plants. The purpose of this study is to determine the technical process of making vegetable pesticides in minimizing the use of chemical pesticides. And knowing the effectiveness and efficiency of using BIO-Smart Planters in overcoming these problems. From the results of application tests that have been carried out in the field, it is proven that the four types of organic material used can eradicate flea pests quickly or with a contact system. All types of materials used in the process of making natural pesticides contain different active ingredients and functions. The results of the research conducted show that BIO-Smart Planters are made from natural ingredients such as tobacco, garlic, chili and soursop leaves where all the ingredients contain active substances capable of killing aphids on eggplant plants (Solanum melongena L.)